Dissecting the roles of peptidoglycan synthetic and autolytic activities in the walled to L-form bacterial transition - Kawai, Yoshikazu; Errington, Jeff (Frontiers in Microbiology, 2023)
Bacterial cells are surrounded by a peptidoglycan (PG) wall, which is a crucial target for antibiotics. It is well known that treatment with cell wall-active antibiotics occasionally converts bacteria to a non-walled “L-form” state that requires the loss of cell wall integrity. L-forms may have an important role in antibiotic resistance and recurrent infection. Recent work has revealed that inhibition of de novo PG precursor synthesis efficiently induces the L-form conversion in a wide range of bacteria, but the molecular mechanisms remain poorly understood. Growth of walled bacteria requires the orderly expansion of the PG layer, which involves the concerted action not just of synthases but also degradative enzymes called autolysins. Most rod-shaped bacteria have two complementary systems for PG insertion, the Rod and aPBP systems. Bacillus subtilis has two major autolysins, called LytE and CwlO, which are thought to have partially redundant functions. We have dissected the functions of autolysins, relative to the Rod and aPBP systems, during the switch to L-form state. Our results suggest that when de novo PG precursor synthesis is inhibited, residual PG synthesis occurs specifically via the aPBP pathway, and that this is required for continued autolytic activity by LytE/CwlO, resulting in cell bulging and efficient L-form emergence. The failure of L-form generation in cells lacking aPBPs was rescued by enhancing the Rod system and in this case, emergence specifically required LytE but was not associated with cell bulging. Our results suggest that two distinct pathways of L-form emergence exist depending on whether PG synthesis is being supported by the aPBP or RodA PG synthases. This work provides new insights into mechanisms of L-form generation, and specialisation in the roles of essential autolysins in relation to the recently recognised dual PG synthetic systems of bacteria.